The results of the pilot study of the Sibling relationship - К. Муса; М. Кабакова; В. Кудрявцев; В. Белолы; Н. Белолы (Хабаршы. Психология және социология сериясы)
The relevance of the research problem is due to the low level of study in Kazakh psychology. The purpose of this study is to confirm the effectiveness of the selected mixed methods for studying sibling relationships, since in previous studies of sibling relationships, blank methods were mainly used. The scientific and practical significance of this study lies in conducting an experiment using a cybernometer device supplemented with valid techniques. The work tested the hypothesis that the relationship of adult siblings can be influenced by the age difference between them, gender, lack of joint activity. The study involved 18 subjects (9 pairs) aged from 14 to 50 years. At the 1st stage of the study, all subjects participated in an experiment on a cybernometer with their siblings, and at the 2nd stage, all siblings answered a specially prepared battery of questionnaires. Such features as empathy in sibling relationships and trust in each other, revealed during the experiment, were also revealed as a result of the survey. The value of the research lies in expanding the scope of the cybernometer device in psychological research. The data obtained from sibling subjects who performed tasks according to specific instructions on a cybernometer are confirmed by the results of standardized techniques. It has been proven that the relationship between siblings is influenced by the age difference between them and the gender of the siblings. The conducted pilot study confirmed the correctness of the chosen methods for studying sibling relationships, and they can be used in the main study.